Density, viscosity, excess molar volume and viscosity deviation for [chloroform (1) + di-isopropyl- ether(2) + 1-propanol (3)] ternary system at 298.15 K - Medina Naessens, Ruth Natalia (2018)
Densities ρ and viscosity η of the [chloroform (1) + di-isopropyl ether (DIPE) (2) + 1-propanol (3)] ternary system have been measured at 298.15 K and pressure of 960 hPa using an Anton Paar DMA 500 stavigmeter. Excess molar volumes VE and viscosity deviation Δη were calculated. The excess molar volume VE and viscosity deviation Δη for binary and ternary systems were correlated by a Redlich-Kister and Nagata and Tamura type equation. Also, the ternary excess molar volume and viscosity deviation Y123 E were predicted using the Radojković equation. From the macroscopic behavior inferences were made about the molecular interactions in the ternary mixture.